Assessing uncertainty in Europe and the US - Is there a common factor? - Oliver Sauter (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2012)
This paper aims an empirical investigation of uncertainty in the Euro Zone as well as the US. For this purpose I conduct a factor analysis of uncertainty measures starting in 2001 until the end of 2011. I use survey-based data provided by the ECB and the Federal Reserve Bank of Philadelphia as well as the stock market indices VSTOXX and VIX, both measures of implied volatility of stock market movements. Each measure shows an increase in uncertainty during the last years marked by the financial turmoil. Given the rise in uncertainty, the question arises whether this uncertainty is driven by the same underlying factors. For the Euro Zone, I show that uncertainty can be separated into factors of short and long-term uncertainty. In the US there is a sharp distinction between uncertainty that drives stock market and real variables on the one hand and inflation (short and long-term) on the other hand. Combining both data sets, factor analysis delivers (1) an international stock market factor, (2) a common European uncertainty factor and (3) an US-inflation uncertainty factor.
urn:nbn:de:bsz:100-opus-7212
Keywords: C1; E3; E5; E6; 330; monetary policy; uncertainty; survey forecast; forecast disagreement; factor analysis